The Werther effect following the suicides of three korean celebrities (2017-2018): an ecological time-series study - Li-Hyun Kim; Gyeong-Min Lee; Woo-Ri Lee; Ki-Bong Yoo (BMC, 2023)
Abstract Background The suicide rate in Korea was the highest among the member countries of the Organization for Economic Cooperation and Development(OECD) for 2013-2016 and 2018-2020. In korea, suicide was the leading cause of death among individuals aged 10-39, and the second leading cause of death for aged 40-59. Thus, this study aimed to examine the Werther effect of the suicides of three Korean idol singers (Jonghyun: December 18, 2017, Sulli: October 14, 2019, and Hara Gu: November 24, 2019). Methods The study conducted Poisson regression and used the cause-of-death statistics microdata from 2016 to 2020 provided by Statistics Korea. The case periods ranged from the day of the suicide of each celebrity to 10 weeks after. The control periods were all weeks from 2016 to 2020, excluding the case periods. Results The suicide rates in Korea significantly increased by 1.21, 1.30, and 1.28 times after the deaths of Jonghyun, Sulli, and Hara Gu, respectively. The Werther effect was more evident in women than men. Suicide rate among individuals aged 10-29 years was greater than those for other age groups. Conclusions This study confirmed that the rate of copycat suicides increased after three celebrity singers in Korea died by suicide. Nevertheless, the rate of suicide after the suicide of the three celebrity singers was lower than those in previous studies in Korea.